Human and Porcine Marginal Chordal Forces in a Vacuum Based Physiological In Vitro Mitral Valve Model - Mads V. Ancker; Sam E. Stephens; Justin T. Jack; Neil B. Ingels; Jonathan F. Wenk; Søren N. Skov; Surendra K. Chawla; Ajit. P. Yoganathan; Morten O. Jensen (Cardiovascular Engineering and Technology, 2026)
Introduction This study aimed to quantitatively investigate the role of marginal chordae of the mitral valve during static closure by analyzing the force within these chordae and its potential correlation with the transvalvular pressure. Materials and Methods Porcine (n = 10) and human (n = 4) mitral valves were mounted in a saddle-shaped annulus clamp, while an in vitro system was utilized to replicate a physiological systolic blood pressure by vacuum pressure applied to the atrial side of the valve. A Millar pressure catheter and force transducers (“C-gauges”) were used to acquire the data. Strut chordal force was recorded simultaneously with the marginal chordal force, to serve as a verification of the employed equipment. Results The marginal chordal force in porcine and human averaged to 0.012 N ± 0.008 N and 0.006 N ± 0.008 N respectively at peak systolic pressure of 120 mmHg. Additionally, a simplified finite element study was conducted and supports low marginal forces relative to intermediary chords. Discussion & Conclusion This low force calls into question the traditionally-described role of the marginal chordae in preventing mitral prolapse at closure. The chords do, however, still show signs of assisting with the leaflets’ positioning. The relationship between marginal chordal forces and transvalvular pressure varies significantly across experiments, further obfuscating their role in normal valvular function.

In silico design, synthesis of a novel chalcone derivative and its in vitro and in vivo anticancer activity against colon cancer-induced mouse model - Uday Raj Sharma; Sushavan Roy; Gurubasavaraja Swamy Purawargaar Matada; Manjunatha P M; Suresh Janadri; Surendra Vada; T. Haribabu; Nageena Taj; Gayathri S V; Rohit Pal; Susovan Das; Nirmal Chanda (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Efficacy and Economic Viability of Biopolymer-Based Trichoderma as a Sustainable Alternative to Emerging Fungicides for Managing Safflower Soil-Borne Diseases - P. Surendra; Suma Moka; M. Kavya; R. D. Prasad; K. S. V. P. Chandrika; D. Murumkar; Reddy T. Rajeshwar; N. Prabhavathi; C. V. Ambadkar; L. Tandon Ashwarya (Journal of Crop Health, 2025)

Plant diversity and microbial interaction on soil carbon stock in the tropical homegardens: a nature-based solution to climate change - Athulya Tom; V. Divya Vijayan; T. K. Kunhamu; S. Sandeep; K. Surendra Gopal; V. Jamaludheen; B. R. Vishnu (Agroforestry Systems, 2025)

Effect of groundwater nutrients on coastal phytoplankton community composition in the Bay of Bengal, India: An experimental study - D. Bhaskara Rao; T. Surendra; Ch.N.V. Laxmi; K.M. Meera; G.V.M. Gupta; B.S.K. Kumar (Marine Pollution Bulletin, 2024)

Immune Mechanisms in Alzheimer’s Disease: The Role of Toll-Like Receptors Signalling - Dinisha Sharma; P. M. Manjunatha; T. Hari Babu; Arpan Dhungel; Sushree Swaraj; Suresh Janadari; Uday Raj Sharma; V. Surendra; Nageena Taj; S. V. Gayathri (Current Pharmacology Reports, 2024)

Evaluation of chicory leaf extract on chronic kidney disease model in streptozotocin-induced diabetic nephropathy - Simran Sultana; Uday Raj Sharma; Reddibathina Leela Haripriya; Athira Ramachandran; Runashree Borah; V. Surendra; T. Haribabu; S. V. Gayathri; Suresh Janadri; P. M. Manjunatha (Advances in Traditional Medicine, 2024)

Rheumatoid arthritis-associated complications during pregnancy and its effect on offspring: comprehensive review - S. Rohini; Uday Raj Sharma; M. Vinutha; D. Shreelaxmi; Surendra Vada; Suresh Janandri; T. Haribabu; Nageena Taj; S. V. Gayathri; Abhishek Ghara; Manjunatha P. Mudagal (Inflammopharmacology, 2024)

Variability of Particulate Amino Acids and Processes Responsible for Sources into the Coastal Waters of the Bay of Bengal - B. S. K. Kumar; D Bhaskara Rao; T. Surendra; Ch. V. Rao; M. P. Meshram (Estuaries and Coasts, 2024)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

G × E interactions in QTL introgression lines of Spanish-type groundnut (Arachis hypogaea L.) - A. L. Rathnakumar; Surendra S. Manohar; Hajisaheb L. Nadaf; Sudam C. Patil; Milind P. Deshmukh; P. P. Thirumalaisamy; Narendra Kumar; H. B. Lalwani; P. Nagaraju; Basavaraj Yenagi; S. S. Patil; J. Suryawanshi; et al. (Euphytica, 2020)

Metagenomic analysis provides insights into functional capacity in a hyperarid desert soil niche community - Surendra Vikram; Leandro D. Guerrero; Thulani P. Makhalanyane; Phuong T. Le; Mary Seely; Don A. Cowan (Environmental Microbiology, 2016)
Summary In hyperarid ecosystems, macroscopic communities are often restricted to cryptic niches, such as hypoliths (microbial communities found beneath translucent rocks), which are widely distributed in hyperarid desert environments. While hypolithic communities are considered to play a major role in productivity, the functional guilds implicated in these processes remain unclear. Here, we describe the metagenomic sequencing, assembly and analysis of hypolithic microbial communities from the N amib D esert. Taxonomic analyses using S mall S ubunit phylogenetic markers showed that bacterial phylotypes (93%) dominated the communities, with relatively small proportions of archaea (0.43%) and fungi (5.6%). Refseq‐viral database analysis showed the presence of double stranded DNA viruses (7.8% contigs), dominated by C audovirales (59.2%). Analysis of functional genes and metabolic pathways revealed that cyanobacteria were primarily responsible for photosynthesis with the presence of multiple copies of genes for both photosystems I and II , with a smaller but significant fraction of proteobacterial anoxic photosystem II genes. Hypolithons demonstrated an extensive genetic capacity for the degradation of phosphonates and mineralization of organic sulphur. Surprisingly, we were unable to show the presence of genes representative of complete nitrogen cycles. Taken together, our analyses suggest an extensive capacity for carbon, phosphate and sulphate cycling but only limited nitrogen biogeochemistry.

Marker-assisted introgression of a QTL region to improve rust resistance in three elite and popular varieties of peanut (Arachis hypogaea L.) - Rajeev K. Varshney; Manish K. Pandey; Pasupuleti Janila; Shyam N. Nigam; Harikishan Sudini; M. V. C. Gowda; Manda Sriswathi; T. Radhakrishnan; Surendra S. Manohar; Patne Nagesh (Theoretical and Applied Genetics, 2014)

Minimum population size, genetic diversity, and social structure of the Asian elephant in Cat Tien National Park and its adjoining areas, Vietnam, based on molecular genetic analyses - T. N. C. Vidya; Surendra Varma; Nguyen X. Dang; T. Van Thanh; R. Sukumar (Conservation Genetics, 2007)

Quantitative Bioanalytical Methods Validation and Implementation: Best Practices for Chromatographic and Ligand Binding Assays - C. T. Viswanathan; Surendra Bansal; Brian Booth; Anthony J. DeStefano; Mark J. Rose; Jeffrey Sailstad; Vinod P. Shah; Jerome P. Skelly; Patrick G. Swann; Russell Weiner (Pharmaceutical Research, 2007)

Workshop/conference report—Quantitative bioanalytical methods validation and implementation: Best practices for chromatographic and ligand binding assays - C. T. Viswanathan; Surendra Bansal; Brian Booth; Anthony J. DeStefano; Mark J. Rose; Jeffrey Sailstad; Vinod P. Shah; Jerome P. Skelly; Patrick G. Swann; Russell Weiner (The AAPS Journal, 2007)

A first genetic linkage map of mulberry (Morus spp.) using RAPD, ISSR, and SSR markers and pseudotestcross mapping strategy - M. Venkateswarlu; S. Raje Urs; B. Surendra Nath; H. E. Shashidhar; M. Maheswaran; T. M. Veeraiah; M. G. Sabitha (Tree Genetics & Genomes, 2006)